KANAK IMAGINARIES: A SENSE OF PLACE IN THE WORK OF DÉWÉ GÖRÖDÉ (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
The study of the Kanak imaginary in the work of the first published Kanak (indigenous) New Caledonian writer shows this to be permeated by a sense of place. Rootedness in, and intense community with the land is not incompatible with the fluidity of ancestral criss-crossing of the Pacific or of constant border-crossing(pathways of exchange between groups) but nonetheless remains central. The ‘hinterland’ constituted by the places of the tribu (customary lands) sets up a challenge to the dominance ofNouméa la blanche and Déwé Görödé’s articulation of places of identity re-negotiate the urban/regional or Noumea/Bush/Tribu nexus to counterbalance or contest national (French) imaginaries. Yet Görödé’s work presents both a return to a Kanak Place to Stand and a critical self in process (the latter situated in a ‘no man’s land’). The places in her work are ultimately ‘cognitively dissonant’: the marginal or hinter-land of Kanak imaginaries (the tribu), can hold (to) their own both outside and inside the city yet also open themselves up internally to multiplicity and critique.